Beyond Methodology and Practice: the Burnum Project, a Case-study of international Cooperation in archaeological Research (Archaeologia Adriatica, 2011)
The Burnum Project was conceived in 2005 as a joint research project between the Department of Archaeology of the University of Zadar, the Municipal Museum of Drniš, and the Laboratory of Archaeological topographical Survey of the Department of Archaeology (University of Bologna), under the international aegis of the Centro Studi per l’Archeologia dell’Adriatico (Ravenna, www.arcadria.eu). The aims of the project are to gain knowledge and preserve an important archaeological site in northern central Dalmatia, the Roman settlement of Burnum, in the Krka River valley. The methodological point of the Burnum Project is to test a protocol of intervention based on the concept of preventive archaeology.
Keywords: Burnum; archaeological documentation; data bases